Acute toxicity, antioxidant and wound healing potential of ethanolic extract of goniothalamus umbrosus in rats / Wasan MJ Hussain Al-Kadmi - Al-Kadmi, Wasan Mj Hussain (2012)
This study was conducted to evaluate the effects of topical application of an ethanol extract of Goniothalamus umbrosus on the rate of skin wound healing closure and the histology of healed wound. The animal groups were topically treated with 0.2 ml of each vehicle (gum acacia), Intrasite gel, 100 and 200 mg/ml of ethanol leaf extract, respectively. An area of uniform wound 2.00 cm in diameter was excised from the nape of the dorsal neck of all rats with the aid of round seal using circular stamp.Macroscopically, skin wound dressed with rhizomes extract and Intrasite gel showed significantly healed earlier than those treated with vehicle.Histological analysis of healed skin wounds dressed with G. umbrosus ethanol leaf extract showed comparatively at wound closure and healed wound contained less inflammatory cells and more collagen with angiogenesis compared to wounds dressed with vehicle. In conclusion, skin wounds dressed with leaf extract showed significantly enhanced the acceleration of wound healing enclosure in rats.